Habitus and Cultural Capital in Higher Education: Chinese Students' Academic and Cultural Adaptation at UK Universities - Ma, Ruoqian (Transactions on Social Science, Education and Humanities Research, 2024)
This paper explores the challenges faced by Chinese students studying in UK universities, drawing on Bourdieu's theories of habitus, capital, and field. It highlights the difficulties encountered due to language and academic culture shocks. Despite these challenges, the paper argues that with agency and resourcefulness, Chinese students can successfully adapt to the academic and cultural environment. The paper concludes that educational institutions have a responsibility to support international students, enabling them to overcome these difficulties and achieve academic success. Future considerations should focus on enhancing cross-cultural understanding and support mechanisms to further facilitate the integration of international students.